Understanding of rhizospheric Cymbopogon citratus-Saphylococcus succinus interactions for phytoremediation of dibenzofuran contaminated soil - Mat Shaari, Nurul Elyni; Zainudin, Zarina; Nordin, Noor Faizul Hadry (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Dioxins or dioxin-like compounds is a group of chloroaromatic compounds which is a highly persistent chemical and accumulates in the environment as well as increasing their distribution in our ecosystem. Phytoremediation is one of the tolerable ways that has been operated to battle out the problem of contaminants. This study investigated how lemongrass (Cymbopogon citratus) ecophysiological traits and soil enzyme activities will be influenced by dibenzofuran (DBF) pollution in rhizospheric zone as a potential remediator. Lemongrass was planted into uncontaminated soil and DBF-contaminated soil. Four treatments were conducted; soil, soil with plant, soil with bacteria, and soil with plant and bacteria. After one month exposure, the plant traits such as leaf and root length, aboveground and belowground mass, chlorophyll content and soil enzymes activities were examined to investigate the sensitivity of lemongrass towards DBF. With the presence of DBF in soil, leaf and root length, and, aboveground and belowground mass were decreased compared to control. However, with inoculation of Staphylococcus succinus in soil, these plant traits were significantly higher than control, suppressing the effects of DBF. The chlorophyll content of lemongrass indicates slightly significance difference showing a less or no effect of DBF. Nevertheless, enzyme activities of asparaginase and protease exhibited higher activity than uncontaminated soil. This shows that lemongrass and Staphylococcus succinus has an interaction within rhizospheric area that might help the degradation of DBF and increase the lemongrass growth.